Aplikasi NPK dan POC Terhadap Pertumbuhan dan Produksi Tomat (Solanum lycopersicun L.) - Waruwu, Impian Berkat; Zulfida, Ida; Jabat, Yelfi Yana Linda Br. (JURNAL AGROPLASMA, 2024)
This study aims to examine the effect of NPK fertilizer and liquid organic fertilizer (POC) application on the growth and production of tomato plants (Solanum Lycopersicum L.). The formulation of the problem raised includes how the application of NPK, POC, and the interaction of both affect plant height, flowering age, number of fruits, fruit weight per sample, and fruit weight per plot. The proposed hypothesis is that the application of NPK, POC, and the interaction of both have a significant effect on tomato growth and production parameters. The study was conducted using a Randomized Block Design (RAK) with two factors, namely the dose of NPK fertilizer (0, 10, 20, and 30 grams per plant) and the dose of POC (0, 200, 400, and 600 ml/L of water). The experiment was carried out in the experimental field of the Faculty of Agriculture, Indonesian Community Development University, Medan, at an altitude of 500 meters above sea level, starting from May 2024 until finished. The parameters observed included plant height, flowering age, number of fruits per sample, fruit weight per sample, and fruit weight per plot. The results showed that the provision of NPK and POC, either singly or in interaction, did not have a significant effect on all observed tomato growth and production parameters. This conclusion indicates that the fertilizer treatment used in this study has not been able to significantly increase the growth and yield of tomato plants. Suggestions for further research are to test higher dose variations and extend the research period to explore the clearer effects of fertilizers. Keywords: tomatoes, NPK, liquid organic fertilizer